A Contrastive and Error Analysis of English Used in Instagram Comments by Indonesian EFL Learners - Siti Ismahani; Mulia Rahmah; Mulia Natasya; Nabilla Anggraini; Indi Hanifah; Naila Al-Zahwa (Abdi Cendekia : Jurnal Pengabdian Masyarakat, 2026)
This qualitative research study examines contrastive errors in English used by Indonesian English as a Foreign Language (EFL) learners in Instagram comments. The research focuses on identifying morphological, syntactic, semantic, and pragmatic errors that reflect the influence of Indonesian language structure and patterns. By analyzing 15 authentic Instagram comments collected from Indonesian users, this study applies contrastive analysis theory to understand how native language interference affects English language production in digital contexts. The findings reveal that Indonesian EFL learners demonstrate specific error patterns including subject-verb agreement violations, article misuse, word order anomalies, and semantic calques from Indonesian. These errors provide valuable insights into the learning process and suggest targeted intervention strategies for improving English proficiency among Indonesian learners in informal digital communication environments.